Artificial Immune System (AIS) Algorithm For Optimizing Shear Zone Temperature In CNC Turning Operation - J.A., Adnan; Minhat, Mohamad; Abd Rahman, Md Nizam (2012)
An Artificial Immune System (AIS) algorithm is proposed as the optimization algorithm to find the optimum cutting parameters that minimize the shear zone temperature. The temperature in metal cutting operations influences the cutting tool properties such as increasing cutting tool wear and reduce the tool life. The shear zone temperature (Ts) effects on the mechanical properties of the cutting tool in CNC turning operation.